2000
DOI: 10.1109/50.908700
|View full text |Cite
|
Sign up to set email alerts
|

Analytical comparison of various fiber-optic CDMA receiver structures

Abstract: Abstract-In this paper, we study the performance of optical code-division multiple access (CDMA) systems using various receivers structures. Two general classes of receivers based on required electronic bandwidth are studied. Optical orthogonal codes (OOCs) are utilized as signature sequences and the performance studied in this paper takes into account the effect of all major noise sources, i.e., quantum shot-noise, dark current noise, and Gaussian circuit noise. Furthermore, this paper introduces a generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 10 publications
1
39
0
2
Order By: Relevance
“…In this work, we develop the structure of a conventional correlation receiver (CCR: Conventional Correlation Receiver) [5]. Figure 2 shows the principle of detection and estimation of the transmitted data, and which comprises 3 functions:…”
Section: Reception System Of Ds-ocdmamentioning
confidence: 99%
“…In this work, we develop the structure of a conventional correlation receiver (CCR: Conventional Correlation Receiver) [5]. Figure 2 shows the principle of detection and estimation of the transmitted data, and which comprises 3 functions:…”
Section: Reception System Of Ds-ocdmamentioning
confidence: 99%
“…The cardinality of this code is (2) which is considerably higher than OOC with . For typical values of and [4], we can have, at most, 27 codewords with and 7924 codewords with . Despite the complexity in analyzing the performance of the system in [3], it was shown that the degradation in performance for OOC codes is not severe, and, in fact, under certain conditions such as for fixed number of users and code length , one can increase the weight of the OOC codes such that it will surpass in performance when compared with OOC optical CDMA systems.…”
mentioning
confidence: 99%
“…In [5], a general upper bound on the number of OOC codes was obtained, and it was shown to be (3) To generalize our scheme, we will consider , which implies that we consider all possible codes of length and weight (except the corresponding cyclic shifts) regardless 0090-6778/02$17.00 漏 2002 IEEE of their mutual cross-correlation value. For sufficiently large values of and , the number of generalized OOC codes is approximately equal to (4) which could be extremely large for typical values of and . However, it remains to be seen that the performance of such optical CDMA systems is not severely degraded.…”
mentioning
confidence: 99%
“…This system utilizes an active correlation receiver where the integration time after the photodetector is in T seconds. Thus, this receiver requires a lower speed electronic design compared with passive correlation receivers [41].…”
Section: Introductionmentioning
confidence: 99%